Major expansion in the human niche preceded out of Africa dispersal - Emily Y. Hallett; Michela Leonardi; Jacopo Niccolò Cerasoni; Manuel Will; Robert Beyer; Mario Krapp; Andrew W. Kandel; Andrea Manica; Eleanor M. L. Scerri (Nature, 2025)
Abstract All contemporary Eurasians trace most of their ancestry to a small population that dispersed out of Africa about 50,000 years ago (ka)1–9. By contrast, fossil evidence attests to earlier migrations out of Africa10–15. These lines of evidence can only be reconciled if early dispersals made little to no genetic contribution to the later, major wave. A key question therefore concerns what factors facilitated the successful later dispersal that led to long-term settlement beyond Africa. Here we show that a notable expansion in human niche breadth within Africa precedes this later dispersal. We assembled a pan-African database of chronometrically dated archaeological sites and used species distribution models (SDMs) to quantify changes in the bioclimatic niche over the past 120,000 years. We found that the human niche began to expand substantially from 70 ka and that this expansion was driven by humans increasing their use of diverse habitat types, from forests to arid deserts. Thus, humans dispersing out of Africa after 50 ka were equipped with a distinctive ecological flexibility among hominins as they encountered climatically challenging habitats, providing a key mechanism for their adaptive success.